2018
DOI: 10.21451/1984-3143-ar2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Placental contribution to the endocrinology of gestation and parturition

Abstract: In addition to many other functions, the placenta is a source of a vast number of autocrine, paracrine and endocrine factors. However, the spectrum of placental regulatory factors, their concentrations, gestational profiles and roles may differ considerably even between phylogenetically closely related species. Depending on the species, placental regulatory factors of a broad range of molecule classes have been found including (glyco-)proteins, peptides, steroids and prostaglandins. Local placental regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 180 publications
0
24
0
18
Order By: Relevance
“…These findings suggest that CCLs contribute to decreasing PG production and preventing luteolysis during early pregnancy in cows. However, luteolysis by PGF2α is regarded as a prerequisite for the onset of parturition in cows [21]. Additionally, placentomal PG production and conversion from progesterone to estrogen are augmented as parturition progresses [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that CCLs contribute to decreasing PG production and preventing luteolysis during early pregnancy in cows. However, luteolysis by PGF2α is regarded as a prerequisite for the onset of parturition in cows [21]. Additionally, placentomal PG production and conversion from progesterone to estrogen are augmented as parturition progresses [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that glucocorticoids are indirectly involved in the increase in CCR1 expression in bovine placentomes at parturition. In spontaneous parturition, increased cortisol release from the fetal adrenals stimulates PGE2 and estrogen synthesis in the cotyledons [21,26]. The inflammatory activities of PGE2 and estrogen might be involved in regulation of the CCL-CCR system in placentomes.…”
Section: Discussionmentioning
confidence: 99%
“…The bovine placenta is capable of producing estrogens independently of the external supply of C19 precursors, as it expresses all enzymes needed to convert cholesterol into estrogens: side chain cleavage enzyme (CYP11A1), steroid 17-alpha-hydroxylase/17,20 lyase (CYP17A1), 3 beta-hydroxysteroid dehydrogenase/Delta 5➔4-isomerase (HSD3B1) and aromatase (CYP19A1) (reviewed by [2]). We searched our microarray data for the expression of the respective transcripts and found that all were downregulated in TGCs (Additional file 1: Table S1-A) The KEGG pathways and the associated DEGs are shown in the Additional file 1: Table S1-D [18] used immunoelectron microscopy and detected CYP11A1-specific signals only in UTCs, and CYP17A1 was immunolocalized only in UTCs [19].…”
Section: Degs Involved In Endocrine Functions Of the Bovine Placentamentioning
confidence: 99%
“…The GH/PRL hormones regulate numerous physiological processes related to reproduction and lactation in many mammalian species, including cattle [22]. The bovine GH/PRL gene family comprises one GH and one PRL gene each, both expressed in the pituitary gland, and derivatives of the PRL gene (CSH2, PRPs) expressed in the placenta [2,23,24]. The DEGs encoding placentaexpressed GH/PRL representatives were all upregulated in the TGCs (Table 4; Additional file 1: Table S1-A).…”
Section: Degs Involved In Endocrine Functions Of the Bovine Placentamentioning
confidence: 99%
See 1 more Smart Citation